IMPLEMENTASI MIROKREDENSIAL DI INDONESIA: MENGUKUR PENERIMAAN TEKNOLOGI MAHASISWA [THE IMPLEMENTATION OF MICROCREDENTIALS IN INDONESIA: MEASURING STUDENTS’ TECHNOLOGY ACCEPTANCE] - Stefany, Stella; Purba, Herman; Suhendro, Anita; Banjarnahor, Evander (Universitas Pelita Harapan, 2023)
AbstractThis study aimed to analyse the main four major components of the Technology Acceptance Model (TAM) in study participants (N = 275). Study participants are students who enrolled in the full online Micro-Credential Developer Program and participated intensively in both synchronous and asynchronous learning activities. Result indicates that perceived ease of use was not directly correlated with participants' behavioural intent to use. It is predicted that the LMS used did not match the course’s characteristics, there still is much room for improvement in the learning design, and the pre-training of students before the program is implemented needs to be significantly improved. The study also presents a comparison of findings on student acceptance of technology in micro-credential programs conducted in various other countries. Bahasa Indonesia Abstrak Penelitian ini menganalisa 4 elemen utama dalam Technology Acceptance Model (TAM) pada sampel mahasiswa (N-275) yang mengikuti Program Mikro Kredensial Game Developer secara intensif dengan moda pembelajaran full daring secara sinkronus maupun asinkronus. Hasil penelitian menunjukkan Perceived Ease of Use tidak memberikan pengaruh langsung terhadap Behavioural Intention to Use dari responden. Hal ini diduga karena kurangnya tepatnya pemilihan LMS yang digunakan, rancangan pembelajaran yang masih harus ditingkatkan serta kurangnya pelatihan yang diberikan oleh penyelenggara kepada responden sebelum Program ini berlangsung. Penelitian ini juga menyajikan perbandingan hasil kajian penerimaan teknologi mahasiswa dalam program mikro kredensial yang dilakukan di berbagai negara lain.